Peningkatan Literasi Pajak UMKM Melalui Edukasi Instrumen Perpajakan di Desa Sumur Batu - Chandra Ayu Pramestidewi; Yoyok Priyo Hutomo; Rachmat Gunawan; Fitri Nurbaeti; Giva Istilah Mitra; Pera Pujiawati Seftia; Amelia Fitriani; Siti Edeniah (Lembaga Pengembangan Kinerja Dosen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, creating jobs, driving economic growth, and promoting community welfare. Despite their significant contribution, MSMEs still face serious challenges, particularly low tax literacy in rural areas. Lack of understanding of tax obligations, reporting procedures, and the use of digital technology in tax administration contribute to low levels of compliance. This research aims to improve tax literacy among MSMEs through a community-based education and mentoring program in Sumur Batu Village. The Participatory Action Research (PAR) method employed emphasizes the active involvement of MSMEs, village officials, and academics in every stage of the activity, from problem identification and planning to implementation and evaluation. The results of the community service program demonstrate an increase in taxpayer understanding and awareness. Participants began to understand the importance of having a Taxpayer Identification Number (NPWP), the procedures for filing Tax Returns (SPT), and learned how to perform simple tax calculations. They also learned to utilize digital platforms such as e-Filing and e-Forms to support more practical tax compliance. Furthermore, this program fosters more regular financial record-keeping habits and reinforces awareness that tax compliance is not merely an administrative obligation but also a social responsibility and a contribution to sustainable village development. Social transformation is evident in the emergence of local change agents who play a role in disseminating good tax practices to other MSMEs. Thus, this service demonstrates that a community-based educational approach is an effective strategy for improving MSME tax literacy and compliance, while simultaneously strengthening village fiscal independence.